A close look: roving reference in a community college library information commons. Issue 2 (27th April 2020) - Kramer, Eileen Hali
Abstract : Purpose: The purpose of this paper is to answer the questions: What challenges do students face in an information commons and how does roving reference help?. Design/methodology/approach: The author recounts her work roving in her community college information commons and supplements this with an analysis of 1, 500 records from her detailed reference log that compares roving reference results with conventional references and with reference questions as a whole. Findings: Her autoethnography and data reveal that roving substantially increases the number of reference encounters. In addition, her data sheds light on students' struggles with common, productivity software, academic packages and malfunctioning hardware. More importantly, these findings show that roving reference data identify problems that librarians, as stakeholders, can solve. Research limitations/implications: Roving reference in a community college information commons brings students in one library into sharper focus. Roving reference increases the number of reference encounters and the reach of reference service. It also exposes a use-based digital divide that calls for collaboration in the long run and increased point-of-need service immediately. Practical implications: Even data that points to digital divides, hardware issues or other shortcomings and offers empirical evidence of problems for which library staff, unlike student workers, can find long-term solutions. This study shows that it is possible to gather rich and extensive data with minimal personnel and off-the-shelf software. Social implications: A college degree is vital to social mobility and easing inequality. Fluency with academic technology and information is necessary for completing college. Roving reference means more opportunities to teach information and computer fluency at point of need and more opportunities for librarian stakeholders to find and remove obstacles to student learning. Originality/value: This is one of the few, recent studies, autoethnographic or otherwise, on roving reference in a community college library's information commons.